Controls on sand ramp formation in southern Namibia. Issue 1 (18th June 2017) - Rowell, Alex; Thomas, David; Bailey, Richard; Stone, Abi; Garzanti, Eduardo; Padoan, Marta
Abstract: Sand ramps have the potential to provide rich palaeoenvironmental information in dryland regions where proxy records are typically scarce. However, current knowledge of the geomorphic controls and processes of sand ramp formation is limited. This study provides a data‐rich examination of the key factors controlling sand ramp formation. The location and morphology of 75 sand ramps in southern Namibia are examined. The sediments and chronologies of 10 sand ramps are studied in detail using 51 OSL dates and 83 grain‐size and LOI samples. Heavy mineral assemblages are used to determine the provenance of 10 samples and OSL sensitivity is used to explore geomorphic processes of eight samples. Sand ramp morphology can be grouped into one of four classes of increasing size and complexity and is closely linked to the available accommodation space. Heavy mineral assemblages indicate local sediment sources and all 75 studied sand ramps are within 4 km of a large ephemeral river channel or within 5.5 km of a dune field. Therefore, accommodation space and sediment supply are identified as the primary controls of sand ramp formation. Sedimentology and OSL sensitivity suggest a complex interplay of aeolian, fluvial and colluvial processes contribute to sand ramp formation with large variability observed between ramps. Three of the ten dated sand ramps have been present in the Namibian landscape for >100 ka. Eight sand ramps show episodic deposition between >75–12 ka and five show evidence of surface reworking over the past 2 ka. Environmental sensitivity is probably linked to the size and availability of the accommodation space. Therefore, individual sand ramps are expected to reflect local environmental conditions, recording when an abundant sediment supply coincided with available accommodation space, while a regional analysis of multiple sand ramps with chronometric data offers the potential to identify larger scale palaeoenvironmental controls of sediment supply. © 2017 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.